Does Globalization Affect Visitor Arrivals in Pacific Island Developing States? The Case of Fiji - Prakash, Kushneel; Ram, Radhika (Journal of Applied Business and Economics, 2017)
Globalization is not a new phenomenon and the countries in the Pacific region are no exception. However, very few studies in this area have been conducted for these island states. In this study, we analyse the role of globalization on visitor arrivals in Fiji. Using VECM, this paper finds that improvements in globalization index along with its three measures (economic, social and political index) has positive and significant impact on visitor arrivals in Fiji over the 1975–2013 period. The study highlights that Fiji should continue to exploit its globalization opportunities to promote tourism and to create more investment opportunities.